3D-printed external fixation guide combined with video-assisted thoracoscopic surgery for the treatment of flail chest: a technical report and case series - Hu, Meng; Sun, Maolin; Bao, Chuanen; Luo, Junlong; Zhuo, Longcai; Guo, Ming (Frontiers in Surgery, 2023)
Background: Flail chest is a common and serious traumatic condition in thoracic surgery. The treatment of flail chest often includes open reduction and internal fixation, which is relatively traumatic, complicated, and expensive. As three-dimensional (3D) printing technology is widely used in the clinical field, the application of 3D-printed products to chest trauma will become a new treatment option. To date, the use of 3D-printed external fixation guides for flail chests has not been reported. Thus, we aimed to assess the short-term efficacy of a new technology that treated flail chests with an individualized 3D-printed external fixation guide combined with video-assisted thoracoscopic surgery (VATS). This is a provisional file, not the final typeset article Conclusions: The 3D-printed external fixation guide combined with video-assisted thoracoscopic surgery is a novel technique in the treatment of flail chest and is safe, effective, feasible, and minimally invasive, with satisfactory clinical efficacy.